Two new Gammarus species (Crustacea: Amphipoda: Gammaridae) from Zagros Mountains, Iran - Hekmatara, Maryam; Sari, Alireza; Baladehi, Mohammad-Hadi Heidary (Zootaxa, 2011)
The present study tries to focus on describing two new species belonging to genus Gammarus from western Iran along the Zagros Mountains range. The most remarkable feature of Gammarus hegmatanensis sp. n. is the shape of epimeral plate 3, which is sharply pointed posteriorly with a distinct lobate anterior margin. This species has some similarities with and differences from some other species of Gammarus pulex–group such as G. parthicus and G. syriacus. The other species, G. sirvannus sp. n. with elongated eyes is similar to G. duebeni, G. lobifer, G. balutchi and G. loeffleri, but it shows prominent morphological differences and a distinct geographical distribution from these species. These new findings shed more light on the information available on amphipod fauna of Iran.